Factors Triggering Anxiety for Pregnant Women during the Covid 19 Pandemic - Triatmi Andri Yanuarini; Shinta Kristianti; Finta Isti Kundarti; Moh. Ali Mansur; Sumy Dwi Antono (STIKes Patria Husada Blitar, 2023)
Covid-19 infection is more common in expectant mothers. than people who are not expecting. This causes pregnant women to experience anxiety and even depression if they are not treated immediately. The pandemic caused by COVID-19 can psychologically cause increased levels of tension and anxiety brought on by worry about spreading disease and its effects. The objective of the study was to identify the triggering factors for anxiety in during the Covid-19 epidemic, expectant mothers. The design of the study was cross-sectional research design. The sample included several expecting mothers in Mojoroto District, Kediri City as many as 67 respondents. The data collection used questionnaire. The data analysis used ordinal regression. The results showed the p-value of pregnancy complications (0.034), limited food ingredients (0.047), history of depression (0.000), environment (0.001), loss of caregiver (0.000) which meant these variables affected the occurrence of anxiety during the Covid-19 epidemic in expecting mothers. COVID-19 increased the risk of complications in expecting mothers, besides that social restrictions also caused limited food ingredients, difficulty getting caregivers. This caused pregnant women to experience depression. The covid pandemic had also caused many deaths and generating worry in expectant mothers. The conclusion is that the triggering factors for pregnancy-related stress and the Covid-19 epidemic pregnancy complications, limited food ingredients, a history of depression, anxiety about the environment and anxiety about losing a caregiver